Epoxy resin emulsion and preparation process thereof

Through the ring-opening reaction of composite polyetheramine and epoxy resin and the use of conductive enhancer, the problem of insufficient stability of epoxy resin emulsion is solved, and the high stability and acid-base salt resistance and high temperature performance of the emulsion are achieved to avoid Precipitation and stratification phenomena.

CN118813000BActive Publication Date: 2024-12-24YANTAI RUIZE CHEM PROD CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411296019.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-24
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

环氧树脂乳液在长期储存时易出现破乳、沉淀和分层,稳定性不足,影响其使用效果。

Method used

Compound polyetheramine mixed with epoxy resin for ring-opening reaction, combined with conductive enhancers such as double-layer microspheres, improve the emulsification effect and stability of the emulsion and enhance its ability to disperse electrostatic charges. The preparation process includes mixing and heating Reaction and dilution steps.

Benefits of technology

It significantly improves the stability and storage time of the epoxy resin emulsion, enhances its acid and alkali salt resistance and high temperature resistance, avoids precipitation and stratification, and ensures the long-term stability and performance of the emulsion.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the field of polymer materials, and specifically discloses an epoxy resin emulsion and a preparation process thereof. An epoxy resin emulsion and a preparation process thereof include the following raw materials in parts by weight: 30-60 parts of epoxy resin, 10-17 parts of composite polyether amine, 1-5 parts of surfactant, 0.5-2.5 parts of conductive enhancer, 0.1-1 parts of preservative, and 30-50 parts of water. In addition, the preparation method of the present application has the advantage of improving the stability of the epoxy resin emulsion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of polymer materials, and more specifically, to an epoxy resin emulsion and a preparation process thereof. Background Art

[0002] Epoxy resin emulsion is a stable emulsion composed of epoxy resin, emulsifier and water. Epoxy resin emulsion has good chemical resistance, corrosion resistance, electrical insulation and high mechanical strength. It can be widely used in coatings, adhesives, composite materials and other fields. In the field of coatings, epoxy resin emulsion can improve the corrosion resistance, weather resistance and adhesion of coatings. During use, you can choose the appropriate type of epoxy resin emulsion according to specific needs, and use and store it correctly according to the product instructions to ensure its best performance.

[0003] Epoxy resin emulsion can be used in the production of carbon fiber, glass fiber and water-based coating. Carbon fiber has good mechanical properties and can effectively improve the strength of composite materials, such as the mechanical properties of organic resin materials, etc., but the surface activity of carbon fiber is low. When compounded with other materials, the interface bonding effect is poor and the dispersion is poor. Therefore, when carbon fiber is used, a sizing agent (i.e. epoxy resin emulsion) is often required to increase the subsequent composite effect of carbon fiber; epoxy resin emulsion is used as a wetting agent in the production of glass fiber. During the production process of glass fiber, the surface of glass fiber is protected, and the generation of static electricity is reduced, which is convenient for the processing and compounding of glass fiber; epoxy resin emulsion as a water-based coating has good anti-corrosion performance, wear resistance and excellent adhesion. However, when epoxy resin emulsion is used, there are also problems. The emulsion system is prone to demulsification, precipitation and stratification during long-term storage, and the stability is insufficient, which affects the use effect of epoxy resin emulsion. Summary of the invention

[0004] In order to improve the stability of epoxy resin emulsion, the present application provides an epoxy resin emulsion and a preparation process thereof.

[0005] In a first aspect, the present application provides an epoxy resin emulsion, which adopts the following technical solution:

[0006] An epoxy resin emulsion comprises the following raw materials in parts by weight: 30-60 parts of epoxy resin, 10-17 parts of composite polyether amine, 0.5-2.5 parts of conductive enhancer, 1-5 parts of surfactant, 0.1-1 part of preservative and 30-50 parts of water.

[0007] By adopting the above technical scheme, after the epoxy resin and the composite polyetheramine are mixed, a ring-opening reaction can be carried out, and the reaction product has a good emulsification effect. After being mixed with the epoxy resin, the emulsification effect of the epoxy resin emulsion is better, the particle size of the emulsion is reduced, and the distribution of the emulsion particles is more uniform, which can make the carbon fiber after sizing have good bundling and fiber opening properties. At the same time, the emulsion particles are not easy to collide with each other, thereby improving the storage time of the emulsion, and it is not easy to aggregate, settle and stratify during long-term storage. At the same time, the acid, alkali and high temperature resistance of the emulsion system can be improved; the conductive enhancer has conductive properties and can conduct and evacuate the static charge generated by the emulsion during storage, which is beneficial to maintaining the electrical balance of the emulsion system and improving the stable storage time of the epoxy resin emulsion.

[0008] Preferably, the composite polyetheramine comprises polyether monoamine, polyether diamine and polyether polyamine in a mass ratio of (1-1.37):(0.52-0.64):(0.76-0.83).

[0009] By adopting the above technical scheme, polyether monoamine, polyether diamine and polyether polyamine are compounded to form a composite polyether amine. After the composite polyether amine is mixed with the epoxy resin, the emulsifier formed by the ring-opening reaction has a better emulsification effect on the epoxy resin emulsion, the obtained epoxy resin emulsion has a smaller particle size, the epoxy resin emulsion has a higher stability, and has good storage stability, acid, alkali and salt resistance and high temperature resistance.

[0010] Preferably, the polyether monoamine is any one of M-600, M-1000 and M-2070, the polyether diamine is any one of D-400 and ED-600, and the polyether polyamine is T-304.

[0011] By adopting the above technical scheme, M-600, M-1000 and M-2070 all have good lubrication effect, D-400 and ED-600 have good compatibility with resin and high reaction rate, T-304 has low volatility and good antioxidant performance, the composite polyetheramine formed by compounding can react with epoxy resin faster, the emulsifier prepared by the reaction has good lubrication and emulsification properties, and the emulsifier has good compatibility with epoxy resin and is mixed more evenly, which is conducive to the full emulsification of epoxy resin emulsion, thereby improving the storage stability, acid, alkali and salt resistance and high temperature resistance of the emulsion.

[0012] Preferably, the conductive enhancer comprises double-layer microspheres, the inner layer of the double-layer microspheres is hollow silicon dioxide microspheres, and the outer layer of the double-layer microspheres is a polyaniline-ferroferric oxide composite layer.

[0013] By adopting the above technical scheme, the inner layer of the double-layer microspheres is hollow silica microspheres, and the hollow silica has good supporting force and impact resistance, so that the double-layer microspheres have good mechanical properties, and the outer layer of the composite microspheres is a polyaniline-ferroferric oxide composite layer, and the polyaniline-ferroferric oxide composite layer has good electrical conductivity, can improve the antistatic property of the emulsion, is conducive to the conduction of static charge in the emulsion, maintains the electrical balance in the emulsion system, and makes the emulsion less prone to precipitation, stratification, etc. At the same time, after the epoxy resin emulsion is sizing the carbon fiber, the carbon fiber has better mechanical properties and antistatic properties.

[0014] Preferably, the preparation method of the double-layer microspheres comprises the following steps: modifying the hollow silica microspheres with a silane coupling agent, adding water and polyvinyl pyrrolidone, stirring until the hollow silica microspheres are completely dispersed, adding styrene and m-divinylbenzene, heating to 80-85° C. under a nitrogen atmosphere, slowly dripping a potassium persulfate aqueous solution, reacting for 23-24 hours, and centrifuging to obtain intermediate microspheres;

[0015] The intermediate microspheres are dispersed in water, aniline is added and stirred evenly, and ammonium persulfate is added dropwise. After reacting for 23-24 hours, the mixture is centrifuged and dried in vacuum to obtain composite microspheres. The composite microspheres are dispersed in ammonia water and immersed for 12-12.5 hours, and then dispersed in water. A mixed solution of ferrous chloride and ferric chloride is added. The mixture is heated to 80-90° C. under a nitrogen atmosphere, stirred for 3-3.5 hours, allowed to stand, and centrifuged. N,N-dimethylformamide is added and mixed evenly. After immersion for 23-24 hours, the mixture is centrifuged, separated, and dried to obtain double-layer microspheres.

[0016] By adopting the above technical scheme, styrene is polymerized on the outer layer of the hollow silica microsphere to form a polystyrene layer, and aniline is polymerized on the outer layer of the polystyrene layer to form a polyaniline layer under the initiation of ammonium persulfate. Polyaniline has good electrical conductivity, so that the double-layer microspheres can conduct static charges in the emulsion, and ferrous chloride and ferric chloride are impregnated into the composite microspheres to form nano-ferroferric oxide particles after heating. The appropriate addition of ferroferric oxide can improve the electrical conductivity of polyaniline, thereby further improving the electrical conductivity of the double-layer microspheres, which is beneficial to the electrostatic balance of the epoxy resin emulsion system.

[0017] Preferably, the intermediate microspheres are further treated as follows: the intermediate microspheres are dispersed in concentrated sulfuric acid, reacted at 45-50° C. for 1.8-2 hours, and then washed, centrifuged, and separated.

[0018] By adopting the above technical solution, the intermediate microspheres are sulfonated, and the sulfonated intermediate microspheres can be better dispersed in water. At the same time, sulfuric acid can be used as a dopant to make aniline better adsorbed on the sulfonation layer, thereby promoting the uniform formation of the polyaniline layer.

[0019] Preferably, the hollow silica microspheres are further pretreated as follows: the hollow silica microspheres are dispersed in a ferrous sulfate solution, stirred and potassium borohydride is slowly dripped in until no bubbles emerge, and then filtered, washed and dried.

[0020] By adopting the above technical solution, after the silica hollow microspheres are treated, the silica hollow microspheres are loaded with nano-iron particles, so that the conductivity of the silica hollow microspheres is improved, and the conductivity of the double-layer microspheres is further improved, thereby improving the electrostatic charge conduction performance of the epoxy resin emulsion during storage, which is beneficial to improving the stability of the epoxy resin emulsion.

[0021] In a second aspect, the present application provides a process for preparing an epoxy resin emulsion, which adopts the following technical solution:

[0022] A method for preparing an epoxy resin emulsion comprises the following steps: mixing epoxy resin, composite polyether amine, surfactant and conductive enhancer, heating to 90-120°C, reacting for 2-7h while stirring, cooling to 50-70°C, adding water for dilution, cooling to 25-35°C, adding preservative and stirring evenly to obtain the epoxy resin emulsion.

[0023] By adopting the above technical scheme, the epoxy resin and the composite polyether amine are mixed and reacted to generate an emulsifier, and after being stirred evenly so that the emulsifier, epoxy resin, surfactant and conductive enhancer are evenly mixed, water is added to obtain an epoxy resin emulsion. The emulsion particles of the epoxy resin emulsion are small in size, evenly distributed, and the emulsion is stable.

[0024] In summary, this application has the following beneficial effects:

[0025] 1. Since the present application adopts a composite polyetheramine to react with an epoxy resin to obtain a product with an emulsifying effect, and after mixing with the remaining epoxy resin, water is added to obtain an epoxy resin emulsion, the product of the ring-opening reaction has a good emulsifying effect, and the particle size of the emulsion particles of the epoxy resin emulsion is reduced and evenly distributed, which is beneficial to improving the bundling and fiber opening of the carbon fiber after sizing. At the same time, the emulsion particles are not prone to collision, thereby increasing the storage time of the emulsion and making the epoxy resin emulsion more stable;

[0026] 2. In the present application, composite polyetheramine is preferably used. Composite polyetheramine is composed of polyether monoamine, polyether diamine and polyether polyamine. The composite polyetheramine is relatively active and has good compatibility and reaction rate with epoxy resin. At the same time, the reaction product has good emulsification properties, thereby improving the stability of epoxy resin emulsion;

[0027] 3. In the present application, double-layer microspheres are preferably used as conductive enhancers. The inner layer of the double-layer microspheres is hollow silica microspheres, and the outer layer of the double-layer microspheres is a polyaniline-ferroferric oxide composite layer. The hollow silica microspheres have good supporting force and impact resistance, so that the double-layer microspheres have good mechanical properties, and the polyaniline-ferroferric oxide composite layer has good electrical conductivity, which can effectively improve the antistatic properties of the emulsion, is beneficial to the conduction of static charges in the emulsion, and maintains the electrical balance in the emulsion system, thereby improving the stability of the epoxy resin emulsion. DETAILED DESCRIPTION

[0028] The present application is further described in detail below in conjunction with embodiments.

[0029] Preparation Example 1 of Silica Hollow Microspheres

[0030] 5.9 g of polystyrene latex with a solid content of 50% was dispersed in 100 mL of ethanol, ultrasonicated for 12 min, 20 mL of 10 wt % ammonia water was added and stirred for 20 min to obtain a mixture, 20 wt % ethyl orthosilicate ethanol solution was slowly added dropwise to the mixture, stirred at room temperature for 12 h and then allowed to stand, washed alternately with water and ethanol three times, centrifuged, dried at 75 ° C to constant weight, and calcined at 550 ° C to remove polystyrene to obtain silica hollow microspheres.

[0031] Preparation Example 2-11 of Double-layer Microspheres

[0032] Preparation Example 2

[0033] 0.2 g of the hollow silica microspheres prepared in Preparation Example 1 were dispersed in 100 mL of an ethanol solution of a silane coupling agent KH-550, with a volume ratio of the silane coupling agent to ethanol of 1:1.2. After immersion for 1 h, the mixture was centrifuged and dried, and then 190 mL of water and 0.9 g of polyvinyl pyrrolidone were added. The mixture was stirred until the hollow silica microspheres were completely dispersed, and then 1.9 mL of styrene and 0.12 mL of m-divinylbenzene were added. The mixture was heated to 80° C. under a nitrogen atmosphere, and 4 mL of a 0.003 g / mL potassium persulfate aqueous solution was slowly dripped in. After reacting for 24 h, the mixture was centrifuged to obtain intermediate microspheres.

[0034] 1 g of the intermediate microspheres was dispersed in 60 mL of water, 0.3 g of aniline was added and stirred evenly, and then 1 mL of 1 mol / mL ammonium persulfate solution was added dropwise. After reacting for 24 hours, the mixture was centrifuged and dried in vacuum to obtain composite microspheres. 1 g of the composite microspheres was dispersed in 50 mL of 10 wt% ammonia water and immersed for 12.5 hours, then dispersed in 100 mL of water, and 5 mL of a mixed solution containing 0.26 mol / L ferrous chloride and 0.51 mol / L ferric chloride was added. The mixture was heated to 80°C under a nitrogen atmosphere, stirred for 3.5 hours, allowed to stand, and then centrifuged and dispersed in 50 mL of N,N-dimethylformamide. After being immersed for 23 hours, the mixture was centrifuged, separated, and dried to obtain double-layer microspheres.

[0035] Preparation Example 3

[0036] 0.23 g of the hollow silica microspheres prepared in Preparation Example 1 were dispersed in 100 mL of an ethanol solution of a silane coupling agent KH-550, wherein the volume ratio of the silane coupling agent to the ethanol was 1:1.26. After immersion for 1.2 h, the mixture was centrifuged and dried, and then 200 mL of water and 0.11 g of polyvinyl pyrrolidone were added. The mixture was stirred until the hollow silica microspheres were completely dispersed, and then 2.1 mL of styrene and 0.15 mL of m-divinylbenzene were added. The mixture was heated to 85° C. under a nitrogen atmosphere, and 3.5 mL of an aqueous potassium persulfate solution having a concentration of 0.004 g / mL was slowly added dropwise. After reacting for 23 h, the mixture was centrifuged to obtain intermediate microspheres.

[0037] 1.2 g of the intermediate microspheres were dispersed in 60 mL of water, 0.46 g of aniline was added and stirred evenly, and then 1.2 mL of 1.1 mol / mL ammonium persulfate solution was added dropwise. After reacting for 23 h, the mixture was centrifuged and dried in vacuum to obtain composite microspheres. 1.1 g of the composite microspheres were dispersed in 60 mL of 12 wt% ammonia water and immersed for 12 h, then dispersed in 120 mL of water, and 7 mL of a mixed solution containing 0.28 mol / L ferrous chloride and 0.55 mol / L ferric chloride was added. The mixture was heated to 90 ° C under a nitrogen atmosphere, stirred for 3 h, allowed to stand, and then centrifuged and dispersed in 60 mL of N, N-dimethylformamide. After immersion for 24 h, the mixture was centrifuged, separated, and dried to obtain double-layer microspheres.

[0038] Preparation Example 4

[0039] The difference between Preparation Example 4 and Preparation Example 2 is that in Preparation Example 4, when preparing the intermediate microspheres, the amount of styrene added is 0.5 mL.

[0040] Preparation Example 5

[0041] The difference between Preparation Example 5 and Preparation Example 2 is that in Preparation Example 5, when preparing the intermediate microspheres, the amount of styrene added is 4 mL.

[0042] Preparation Example 6

[0043] The difference between Preparation Example 6 and Preparation Example 2 is that in Preparation Example 6, the concentrations of ferrous chloride and ferric chloride in the mixed solution are 0.1 mol / L and 0.2 mol / L, respectively.

[0044] Preparation Example 7

[0045] The difference between Preparation Example 7 and Preparation Example 2 is that in Preparation Example 7, the concentrations of ferrous chloride and ferric chloride in the mixed solution are 0.4 mol / L and 0.8 mol / L, respectively.

[0046] Preparation Example 8

[0047] The difference between Preparation Example 8 and Preparation Example 2 is that the intermediate microspheres are further treated as follows: the intermediate microspheres are dispersed in concentrated sulfuric acid, reacted at 45° C. for 2 h, and then washed, centrifuged, and separated.

[0048] Preparation Example 9

[0049] The difference between Preparation Example 9 and Preparation Example 2 is that the intermediate microspheres are further treated as follows: the intermediate microspheres are dispersed in concentrated sulfuric acid, reacted at 50° C. for 1.8 h, and then washed, centrifuged, and separated.

[0050] Preparation Example 10

[0051] The difference between Preparation Example 10 and Preparation Example 2 is that the hollow silica microspheres are further subjected to the following pretreatment: 0.1 g of the hollow silica microspheres are dispersed in 20 mL of a 35 mol / L ferrous sulfate solution, stirred and slowly dripped with 40 mL of 35 mol / L potassium borohydride until no bubbles emerge, filtered, washed, and dried.

[0052] Preparation Example 11

[0053] The difference between Preparation Example 11 and Preparation Example 2 is that the hollow silica microspheres are further subjected to the following pretreatment: 0.12 g of the hollow silica microspheres are dispersed in 15 mL of a 50 mol / L ferrous sulfate solution, stirred and slowly dripped with 30 mL of 50 mol potassium borohydride until no bubbles emerge, filtered, washed, and dried. Example

[0054] Example 1

[0055] An epoxy resin emulsion comprises the following raw materials in parts by weight:

[0056] 30kg epoxy resin, 10kg composite polyether amine, 1kg surfactant, 0.5kg conductive enhancer, 0.1kg preservative and 30kg water, the epoxy resin is bisphenol A epoxy resin, the epoxy equivalent is 100g / eq, the epoxy value is 0.52mol / 100g, the surfactant is compounded by dodecylphenol polyoxyethylene ether, hexadecyltrimethylammonium bromide and octadecyltrimethylammonium bromide in a mass ratio of 1.2:0.8:1.8, wherein the composite polyether amine includes polyether unit amine, polyether diamine and polyether polyamine in a mass ratio of 1:0.52:0.76, the polyether unit amine is M-1000, the polyether diamine is ED-600, and the polyether polyamine is T-304; the conductive enhancer is double-layer microspheres, and the double-layer microspheres are selected from the double-layer microspheres prepared in Preparation Example 2; the preservative is salicylic acid purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0057] The preparation process of the above-mentioned epoxy resin emulsion includes the following steps: mixing epoxy resin, composite polyether amine and conductive enhancer, heating to 90°C, reacting with stirring for 7 hours, cooling to 70°C, slowly adding water while stirring, cooling to 35°C, adding preservatives and stirring evenly to obtain epoxy resin emulsion.

[0058] Example 2

[0059] An epoxy resin emulsion comprises the following raw materials in parts by weight:

[0060] 60kg epoxy resin, 17kg composite polyether amine, 5kg surfactant, 2.5kg conductive enhancer, 1kg preservative and 50kg water, the epoxy resin is bisphenol A epoxy resin, the epoxy equivalent is 100g / eq, the epoxy value is 0.52mol / 100g, the surfactant is a compound of dioctadecyl dimethyl ammonium chloride and lauroyl diethanolamine in a mass ratio of 0.5:1.6, wherein the composite polyether amine includes polyether unit amine, polyether diamine and polyether polyamine in a mass ratio of 1.37:0.64:0.83, the polyether unit amine is M-600, the polyether diamine is D-400, and the polyether polyamine is T-304; the conductive enhancer is a double-layer microsphere, the double-layer microsphere is the double-layer microsphere obtained in Preparation Example 3, and the preservative is benzylamine, which is purchased from Shandong Yuexing Chemical Co., Ltd.

[0061] The preparation process of the above-mentioned epoxy resin emulsion includes the following steps: mixing epoxy resin, composite polyether amine, surfactant and conductive enhancer, heating to 120°C, reacting with stirring for 2 hours, cooling to 50°C, slowly adding water while stirring, cooling to 25°C, adding preservatives and stirring evenly to obtain epoxy resin emulsion.

[0062] Example 3

[0063] The difference between Example 3 and Example 1 is that the composite polyetheramine in Example 3 includes polyether monoamine, polyether diamine and polyether polyamine in a mass ratio of 1:0.4:0.5.

[0064] Example 4

[0065] The difference between Example 4 and Example 1 is that the composite polyetheramine in Example 4 includes polyether monoamine, polyether diamine and polyether polyamine in a mass ratio of 1:0.8:1.

[0066] Example 5

[0067] The difference between Example 5 and Example 1 is that the double-layer microspheres in Example 5 are the double-layer microspheres prepared in Preparation Example 4.

[0068] Example 6

[0069] The difference between Example 6 and Example 1 is that the double-layer microspheres in Example 6 are the double-layer microspheres prepared in Preparation Example 5.

[0070] Example 7

[0071] The difference between Example 7 and Example 1 is that the double-layer microspheres in Example 7 are the double-layer microspheres prepared in Preparation Example 6.

[0072] Example 8

[0073] The difference between Example 8 and Example 1 is that the double-layer microspheres in Example 8 are the double-layer microspheres prepared in Preparation Example 7.

[0074] Example 9

[0075] The difference between Example 9 and Example 1 is that the double-layer microspheres in Example 9 are the double-layer microspheres prepared in Preparation Example 8.

[0076] Example 10

[0077] The difference between Example 10 and Example 1 is that the double-layer microspheres in Example 10 are the double-layer microspheres prepared in Preparation Example 9.

[0078] Embodiment 11

[0079] The difference between Example 11 and Example 1 is that the double-layer microspheres in Example 11 are the double-layer microspheres prepared in Preparation Example 10.

[0080] Example 12

[0081] The difference between Example 12 and Example 1 is that the double-layer microspheres in Example 12 are the double-layer microspheres prepared in Preparation Example 11. Comparative Example

[0082] Comparative Example 1

[0083] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, an equal amount of M-1000 is used to replace the composite polyetheramine.

[0084] Comparative Example 2

[0085] The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, an equal amount of ED-600 is used to replace the composite polyetheramine.

[0086] Comparative Example 3

[0087] The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, an equal amount of T-304 is used to replace the composite polyetheramine.

[0088] Comparative Example 4

[0089] The difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, no conductivity enhancer is added.

[0090] Comparative Example 5

[0091] The difference between Comparative Example 5 and Example 1 is that in Comparative Example 5, the epoxy resin emulsion comprises the following raw materials in parts by weight: 25 kg epoxy resin, 2 kg composite polyether amine, 0.2 kg conductive enhancer and 25 kg water.

[0092] Comparative Example 6

[0093] The difference between Comparative Example 6 and Example 1 is that in Comparative Example 6, the epoxy resin emulsion includes the following raw materials in parts by weight: 40 kg epoxy resin, 25 kg composite polyether amine, 8 kg conductive enhancer and 40 kg water.

[0094] Detection Methods

[0095] 1. Epoxy resin emulsions were prepared according to the raw materials and processes of Examples 1-12 and Comparative Examples 1-6, the particle size of the emulsions was tested using a laser particle size analyzer, and the average particle size of the epoxy resin emulsions was recorded in Table 1.

[0096] 2. Determine the storage stability of the epoxy resin emulsion. Refer to "GB6753.3-86-Test Method for Storage Stability of Coatings" for the storage environment. Test the stability of the epoxy resin emulsion. If the epoxy resin emulsion shows severe stratification and is difficult to restore to its original state after shaking, or stratification occurs soon after returning to its original state, it is considered that the epoxy resin emulsion has deteriorated, and the number of days of deterioration is recorded in Table 1.

[0097] 3. Determination of acid, alkali and salt resistance of epoxy resin emulsion: prepare 100g / L acetic acid solution, 100g / L sodium hydroxide solution and 100g / L sodium sulfate solution for standby use, take 30g of the prepared epoxy resin emulsion, add water to make up to 100g in each group of 10g to prepare a sample, add acetic acid solution, sodium hydroxide solution and sodium sulfate solution respectively, stir for 5min, and observe the condition of the sample. If there is no stratification, it is recorded as Class A. If there is slight stratification, it can quickly return to its original state after shaking, which is recorded as Class B. If there is obvious stratification, it can return to its original state after shaking, but the recovery speed is slow, which is recorded as Class C. If there is severe stratification and it is difficult to return to its original state after shaking, or stratification occurs again soon after returning to its original state, it is recorded as Class D, and the results are recorded in Table 2.

[0098] 4. Test the high temperature resistance of epoxy resin emulsion: Take 10g of the prepared epoxy resin emulsion, add water to make up to 100g to prepare a sample, place the sample in an 80℃ water bath for 30min, stir every 10min, cool, let stand, and observe the condition of the sample. If there is no stratification, it is recorded as Class A. If there is slight stratification, it can quickly return to its original state after shaking, which is recorded as Class B. If there is a more obvious stratification, it can return to its original state after shaking, but the recovery speed is slow, which is recorded as Class C. If there is a serious stratification and it is difficult to return to its original state after shaking, or stratification reappears soon after returning to its original state, it is recorded as Class D, and the results are recorded in Table 2.

[0099] Table 1 Average particle size and storage stability of epoxy resin emulsion

[0100] project Average particle size / nm Storage stability / d Example 1 72.38 47 Example 2 73.16 46 Example 3 289.13 39 Example 4 276.27 39 Example 5 72.15 42 Example 6 71.39 41 Example 7 73.12 40 Example 8 71.67 41 Example 9 71.64 49 Example 10 72.34 50 Embodiment 11 71.25 51 Example 12 70.98 50 Comparative Example 1 364.13 28 Comparative Example 2 328.16 26 Comparative Example 3 342.94 30 Comparative Example 4 74.59 37 Comparative Example 5 421.96 32 Comparative Example 6 216.75 31

[0101] Table 2 Acid, alkali, salt and high temperature resistance of epoxy resin emulsion

[0102] project Acid resistance Alkali resistance Salt tolerance High temperature resistance Example 1 A A A A Example 2 A A A A Example 3 B B B B Example 4 B B B B Example 5 B B B B Example 6 B B B B Example 7 B B B B Example 8 B B B B Example 9 A A A A Example 10 A A A A Embodiment 11 A A A A Example 12 A A A A Comparative Example 1 D D D D Comparative Example 2 D D D D Comparative Example 3 D D D D Comparative Example 4 A A A A Comparative Example 5 D D D D Comparative Example 6 D D D D

[0103] According to Table 1, Table 2, Examples 1-2 and Comparative Examples 1-6, it can be seen that the average particle size, storage stability, acid, alkali and salt resistance and high temperature resistance of the epoxy resin emulsion prepared in Example 1-2 are better than those in Comparative Examples 1-6, indicating that the epoxy resin emulsion prepared by the raw material ratio and preparation process of Example 1-2 has better performance. Comparative Example 1-3 uses a single type of polyetheramine to replace the composite polyetheramine, indicating that the composite polyetheramine formed by the compounding of polyether monoamine, polyether diamine and polyether polyamine has a faster reaction rate with the epoxy resin, and the reaction product has good lubrication and emulsification properties. The reaction product has good compatibility with the epoxy resin and is mixed more evenly, which is conducive to the reaction product to fully exert the emulsification effect, so that the particle size of the epoxy resin emulsion is smaller and the stability is better. The prepared epoxy resin emulsion is milky white, evenly dispersed without stratification, has good stability and light transmittance, and can be stored stably for a long time.

[0104] No conductive enhancer was added in Comparative Example 4, which indicates that the conductive enhancer is beneficial to improving the stability of the epoxy resin emulsion. The conductive enhancer is added to the epoxy resin emulsion, and the conductive enhancer can form a conductive network, thereby transferring and channeling the static charge generated by the epoxy resin emulsion, so that the static charge generated by the epoxy resin emulsion during the preparation and storage process can be evacuated in time, which is beneficial to maintaining the electrical balance in the epoxy resin emulsion system, making the epoxy resin emulsion less prone to precipitation, stratification, etc.

[0105] In Comparative Examples 5-6, the addition amounts of epoxy resin, composite polyetheramine and conductive enhancer were changed, indicating that the addition amounts of epoxy resin, composite polyetheramine and conductive enhancer would affect the performance of epoxy resin emulsion, and in Examples 1-2, the quality of epoxy resin, composite polyetheramine and conductive enhancer was relatively good, and the obtained epoxy resin emulsion had better performance. Changing the mass ratio between epoxy resin and composite polyetheramine may affect the reaction between epoxy resin and composite polyetheramine and the emulsification properties of their products, while changing the addition amount of conductive enhancer. If the addition amount of conductive enhancer is too small, its reinforcing effect on epoxy resin emulsion will be weakened. If the addition amount is too large, the double-layer microspheres will be unevenly dispersed, affecting the formation of conductive network.

[0106] Compared with Example 1, the average particle size, storage stability, acid, alkali and salt resistance and high temperature resistance of the epoxy resin emulsion prepared in Example 3-4 are inferior to those in Example 1. The composition ratio of the composite polyether amine is adjusted in Example 3-4, indicating that the mass ratio of the polyether unit amine, the polyether diamine and the polyether polyamine in the composite polyether amine has an influence on the performance of the epoxy resin emulsion. The polyether unit amines all have good lubricating effect, the polyether diamines have good compatibility with the resin and a high reaction rate, the polyether polyamines have low volatility and good antioxidant properties, the composite polyether amine formed by the compounding can react with the epoxy resin faster, the emulsifier obtained by the reaction has good lubricating and emulsifying properties, and the emulsifier has good compatibility with the epoxy resin, and the mixing is more uniform, which is conducive to the full emulsification of the epoxy resin emulsion. The composition ratio of Example 1 has a better synergistic effect and the performance of the reaction product is better.

[0107] Compared with Example 1, the average particle size, storage stability, acid, alkali and salt resistance and high temperature resistance of the epoxy resin emulsion prepared in Example 5-6 are inferior to those in Example 1. When preparing the double-layer microspheres in Example 5-6, the amount of styrene added was adjusted. Styrene was polymerized to form a polystyrene layer, so that aniline could be polymerized on the basis of the polystyrene layer to form a polyaniline layer. The amount of styrene added directly affected the thickness and morphology of the polystyrene layer, thereby affecting the formation of the polyaniline layer, so that the morphology and uniformity of the outer polyaniline-ferroferric oxide composite layer were affected, thereby affecting the electrostatic charge conduction effect of the double-layer microspheres.

[0108] Compared with Example 1, the average particle size, storage stability, acid, alkali and salt resistance and high temperature resistance of the epoxy resin emulsion prepared in Example 7-8 are inferior to those in Example 1. When preparing double-layer microspheres in Example 7-8, the concentrations of ferrous chloride and ferric chloride were adjusted. The concentrations of ferric chloride and ferrous chloride directly affect the content of ferric oxide in the polyaniline-ferric oxide layer. The addition of nano-ferric oxide particles can improve the conductivity of polyaniline. When the amount of ferric oxide added is small, the conductivity of polyaniline is less improved. When the amount of ferric oxide added is too much, ferric oxide will destroy the original conductive network of polyaniline, causing the conductivity of the double-layer microspheres to decrease.

[0109] Compared with Example 1, the average particle size, storage stability, acid, alkali and salt resistance and high temperature resistance of the epoxy resin emulsion prepared in Example 9-10 are better than those in Example 1. When preparing double-layer microspheres in Example 9-10, the intermediate microspheres are also treated with concentrated sulfuric acid and the intermediate microspheres are sulfonated, so that the sulfonated intermediate microspheres can be better dispersed in water. At the same time, sulfuric acid as a dopant is beneficial to better adsorption of aniline on the sulfonated layer, thereby promoting the uniform formation of the polyaniline layer.

[0110] Compared with Example 1, the average particle size, storage stability, acid, alkali and salt resistance and high temperature resistance of the epoxy resin emulsion prepared in Example 11-12 are better than those in Example 1. The silica hollow microspheres in Example 11-12 are also pretreated. After the pretreatment, the silica hollow microspheres are loaded with nano-iron particles. The nano-iron particles have good conductivity, thereby improving the conductivity of the silica hollow microspheres, and further improving the conductivity of the double-layer microspheres, which is beneficial to reducing the storage of static charge of the epoxy resin emulsion during storage, and is beneficial to maintaining the electrostatic balance of the emulsion system, thereby improving the stability of the epoxy resin emulsion.

[0111] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An epoxy resin emulsion, characterized in that: The method comprises the following raw materials in parts by weight: 30-60 parts of epoxy resin, 10-17 parts of composite polyether amine, 1-5 parts of surfactant, 0.5-2.5 parts of conductive enhancer, 0.1-1 parts of preservative, and 30-50 parts of water; The composite polyetheramine comprises a polyether unit amine, a polyether diamine and a polyether polyamine in a mass ratio of (1-1.37):(0.52-0.64):(0.76-0.83), the polyether unit amine is any one of M-600, M-1000 and M-2070, the polyether diamine is any one of D-400 and ED-600, and the polyether polyamine is T-304; The conductive enhancer comprises double-layer microspheres, the inner layer of the double-layer microspheres is hollow silicon dioxide microspheres, and the outer layer of the double-layer microspheres is a polyaniline-ferroferric oxide composite layer; The preparation method of the double-layer microspheres comprises the following steps: modifying the hollow silica microspheres with a silane coupling agent, adding water and polyvinyl pyrrolidone, stirring until the hollow silica microspheres are completely dispersed, adding styrene and m-divinylbenzene, heating to 80-85° C. in a nitrogen atmosphere, slowly dripping a potassium persulfate aqueous solution, reacting for 23-24 hours, and centrifuging to obtain intermediate microspheres; The intermediate microspheres are dispersed in water, aniline is added and stirred evenly, and ammonium persulfate is added dropwise. After reacting for 23-24 hours, the mixture is centrifuged and dried in vacuum to obtain composite microspheres. The composite microspheres are dispersed in ammonia water and immersed for 12-12.5 hours, and then dispersed in water. A mixed solution of ferrous chloride and ferric chloride is added. The mixture is heated to 80-90° C. under a nitrogen atmosphere, stirred for 3-3.5 hours, allowed to stand, and centrifuged. N,N-dimethylformamide is added and mixed evenly. After immersion for 23-24 hours, the mixture is centrifuged, separated, and dried to obtain double-layer microspheres.

2. An epoxy resin emulsion according to claim 1, characterized in that: Before being dispersed in water, the intermediate microspheres are further treated as follows: the intermediate microspheres are dispersed in concentrated sulfuric acid, reacted at 45-50° C. for 1.8-2 hours, and then washed, centrifuged, and separated.

3. An epoxy resin emulsion according to claim 1, characterized in that: Before the silicon dioxide hollow microspheres are modified by the silane coupling agent, they are also pretreated as follows: the silicon dioxide hollow microspheres are dispersed in a ferrous sulfate solution, stirred and potassium borohydride is slowly dripped in until no bubbles emerge, and then filtered, washed and dried.

4. A process for preparing an epoxy resin emulsion according to any one of claims 1 to 3, characterized in that: The following steps are involved: The epoxy resin, composite polyetheramine, surfactant and conductive enhancer are mixed, heated to 90-120°C, reacted with stirring for 2-7 hours, cooled to 50-70°C, diluted with water, cooled to 25-35°C, added with preservatives and stirred evenly to obtain epoxy resin emulsion.

Citation Information

Patent Citations

  • Low-VOC (Volatile Organic Compound) self-emulsifying solid epoxy resin water-based emulsion and preparation method thereof

    CN101974162A

  • Water-based heavy-duty anticorrosive epoxy resin emulsion and preparation method thereof

    CN111057443A

  • Water-based polyphenol type epoxy emulsion and preparation method thereof

    CN112898733A

  • Waterborne epoxy resin emulsion as well as preparation method and application thereof

    CN115678390A

  • Aqueous hardeners for epoxy resin systems

    US5854312A